Synthesis and perspectives of bibliographic information on Tapirella bairdii in Mexico - Guevara-Chumacero, Luis Manuel; Rubio-Gutiérrez, Itzel Citlalli; Gordillo Méndez, Carlos Alfredo (THERYA, 2019)
Tapirella bairdii participates in the dynamics of tropical forests through herbivory and seed dispersal. The objective of the present study was to review and analyze the literature published on T. bairdii in México between 1865 and 2018 aiming to identify information gaps and advances in knowledge and propose future research perspectives. The literature references on T. bairdii in México published in periodic scientific journals between 1865 (year of description of the species) and 2018 were organized in the software Endnote Plus. Articles were arranged into 5-year periods to identify publication trends. Articles were grouped according to 1) the 11 main topics, 2) the Mexican state where the study was carried out, 3) country of origin (national or foreign) of the first author, and 4) country of origin of the journal (national or foreign). A total of 136 published articles were recorded, more than eighty-eight percent between 1995 and 2018. Eighty-one percent of studies were carried out by Mexican researchers. These articles were published in 43 foreign and 11 national journals. Seventy-three percent of the studies were carried out in Chiapas, Oaxaca, and Campeche. A total of 233 records of occurrence of T. bairdii in México have been documented. The topics most frequently addressed include ecology, taxonomy and phylogeny, and distribution. No research has been published on physiology and ethology. The most productive years of research (1995-2018) can be explained by the increase in the number of Mexican researchers, with more funds allocated to research projects, information dissemination about the tapir, and the greater economic, scientific, and technological developments in different areas. The participation of national researchers is highlighted, with most articles published in foreign journals. The compilation of published information highlights the need to continue preserving Natural Protected Areas (NPAs), the Mesoamerican Biological Corridor, and unprotected regions that are home to tapir populations. Also, the connectivity between tapir populations should be improved, and the availability of tapir habitats in the country should be warranted. Research is needed to cover information gaps on basic aspects of the biology of the species, including physiology, ethology, diseases and parasitism, genetics, anatomy, reproduction, and evolutionary history, among others. Our findings reveal that no research on the physiology and ethology of tapirs has been conducted. Finally, the formation of a collaborative network to define and prioritize efforts and set guidelines is a priority.